Certified Nurses’ Practice of Palliative Care for Later-Stage Elderly Patients with End-Stage Heart Failure - Okada Sara; Kato Maki; Takeda Yuko; Hara Sachiko (日本看護研究学会雑誌, 2023)
Objective: This study aimed to clarify palliative care practiced by certified nurses in palliative care and certified nurses in chronic heart failure nursing for later-stage elderly patients hospitalized for end-stage heart failure. Methods: Semi-structured interviews were conducted with four certified nurses, and the interview data were analyzed qualitatively. Results: Regarding care provided by certified nurses, eight categories were extracted: [adjust patients’ oxygen consumption in daily activities], [use a non-pharmacological approach to ease patients’ difficulty in breathing], [create a time that allows patients to get relief from their chronic pain and feel comfortable], [involve other people to mitigate patients’ pain], [get support from people around the patient so that he/she can lead his/her daily life without excess treatment burden], [recognize patients who keep fighting despite feeling depressed due to prolonged restrictions on daily life], [relax prolonged restrictions on daily life little by little], and [provide support to make patients’ wishes come true while taking into account their remaining lifetime]. Conclusions: It was suggested that in caring for patients approaching the end of life, it is necessary to provide care while striking a balance between the degree of psychological burden and restrictions on daily life. 目的：末期心不全のため入院している後期高齢患者に対する緩和ケアおよび慢性心不全看護認定看護師の緩和ケア実践を明らかにする。方法：4名の認定看護師を対象に半構造化面接を実施し，データを質的に分析した。結果：【療養生活に伴う酸素消費量を調整する】，【呼吸苦を和らげるために非薬物的アプローチを取り入れる】，【持続する苦痛から心地よいひとときを創り出す】，【苦痛緩和のために周囲を巻き込むという策を講じる】，【過負荷がかからない療養生活を継続できるように周囲の支援を得ていく】，【制限ある療養生活に心がおれそうな患者の頑張りを承認する】，【長きに渡った療養生活の制限を少しずつ緩める】，【残りの時間を意識しながら本人の望みの実現をサポートする】という8つのカテゴリーに集約された。結論：人生の最期に近づくなかで，心負荷の程度と療養生活の制限のバランスを図りながらケアを行っていく必要性が示唆された。